Effect of multi-disciplinary team care program on quality of life, anxiety, and depression in hepatocellular carcinoma patients after surgery: A randomized, controlled study - Yang, Li; Yan, Chenli; Wang, Jingjing (Frontiers in Surgery, 2023)
Objective: Multi-disciplinary team (MDT) collaboration enables hepatocellular carcinoma (HCC) patients to achieve better survival through precise diagnosis and individualized treatment. This study aimed to further investigate the effect of MDT care program (MDT-CP) on quality of life (QoL), anxiety and depression in HCC patients after surgery. Methods: Totally, 150 postoperative HCC patients were enrolled and randomized in a 1:1 ratio into the MDT-CP group (N=76) to receive MDT care for 6 months and the normal care program (N-CP) group (N=74) to receive routine care for 6 months. Results: Quality of Life Questionnaire-Core 30 (QLQ-C30) global health status score at 1 month (M1), M3 and M6, QLQ-C30 functions score at M3 and M6 elevated while QLQ-C30 symptom score at M1 and M3 decreased in MDT-CP group compared with N-CP group (all P<0.05). In addition, Hospital Anxiety and Depression Scale (HADS)-Anxiety score at M3 and M6, anxiety occurrence rate at M6, anxiety degree at M6, were all reduced in MDT-CP group compared with N-CP group (all P<0.05). HADS-Depression score at M6, and depression occurrence rate at M3, were both lessened in MDT-CP group compared to N-CP group (both P<0.05), while there was no distinction of depression degree at any time points between groups. Conclusion: MDT-CP improves QoL, relieves anxiety and depression to a certain extent in HCC patients after surgery.